Analisis Perawatan pada Unit Dump Truck FMX 440 Kapasitas 30 Ton dengan Metode Reliability Centered Maintenance (RCM) - Carman, Dimas Sultannu Ikhsan Aulia Bin; Zainuri, Ach. Muhib (Al-DYAS, 2024)
One of the coal mining activities is to move coal from pit to rom using transport equipment, namely dump trucks. In the case study in the field, the dump truck used is FMX 440 with a capacity of 30 tonnes which operates for 18 hours/day. The obstacles or problems encountered during operations include damage and disruption to the dump truck unit system, which can interfere with the mining process and result in a reduction in the amount of coal production targeted by the landowner. Therefore, other methods are needed so that maintenance can be planned and carried out properly. This research aims to find critical components, and maintenance intervals on dump trucks. This research uses the reliability centreed maintenance (RCM) method. The results obtained are critical components, MTBF and MTTR values are cooling system 5,011.96 hours and 1.44 hours, transmission (T / M) system 14,446.24 hours and 2.75 hours, hydraulic oil hose and piping 22,326 hours and 10.54 hours, and air piping and hose 17,541.86 hours and 4.86 hours. From the calculation of the reliability value of critical components, the maintenance time interval for each component is obtained, namely the cooling system is carried out maintenance after 138 operating days, the transmission (T / M) system is carried out maintenance after 416 operating days, hyd. oil hose & piping is carried out maintenance after 638 operating days, and air piping & hose after 500 operating days.